Retroauricular flap: case report - Douglas Haddad Filho; Flávia Fenólio Nigro Marcelino; Paola Assunção Mendes; Marcela Haddad Parada; Carolina Soutto Mayor Mangini (Surgical & Cosmetic Dermatology, 2021)
Basal cell carcinoma (BCC) can affect the auricular region in several locations and sizes, with or without cartilage involvement. Sometimes resections are small and reconstructions are simple. Other times, when the lesions are more extensive, reconstructions are more complex, considering the limited amount of skin in the area and the peculiarity of the structures involved. We report a case of a retroauricular flap staged in two stages, after the excision of a BCC on the posterior face of the auricle, with partial involvement of the cartilage, showing a great aesthetic and functional result both in the recipient and donor area.